2017
DOI: 10.1007/s00038-017-0960-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of fine particulate matter pollution on daily health events in Latin America: a systematic review and meta-analysis

Abstract: ResultsWe retrieved 1628 studies. Nine were elected for the qualitative analysis and seven for the quantitative analyses. Each 10 µg/m 3 increments in daily PM 2.5 concentrations was significantly associated with increased risk for respiratory and cardiovascular mortality in all-ages (polled RR = 1.02, 95% CI, 1.02-1.02 and RR = 1.01, 95% CI , 1.01-1.02, respectively). Conclusions Short-term exposure to PM 2.5 in LA is significantly associated with increased risk for respiratory and cardiovascular mortality. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 32 publications
4
43
0
7
Order By: Relevance
“…An increase of 10μg/m 3 in daily concentrations of PM 2.5 was significantly associated with increased risk of respiratory mortality in all age brackets (RR = 1.02, 95%CI: 1.02-1.02), and the authors concluded that short-term exposure to PM 2.5 in Latin American cities is significantly associated with increased risk of respiratory mortality. The review also shows that there are still few studies on fine particulate matter 23 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An increase of 10μg/m 3 in daily concentrations of PM 2.5 was significantly associated with increased risk of respiratory mortality in all age brackets (RR = 1.02, 95%CI: 1.02-1.02), and the authors concluded that short-term exposure to PM 2.5 in Latin American cities is significantly associated with increased risk of respiratory mortality. The review also shows that there are still few studies on fine particulate matter 23 .…”
Section: Discussionmentioning
confidence: 97%
“…In a review of 1,628 studies in Latin American cities 23 , nine were selected for the qualitative analysis and seven for the quantitative analyses. An increase of 10μg/m 3 in daily concentrations of PM 2.5 was significantly associated with increased risk of respiratory mortality in all age brackets (RR = 1.02, 95%CI: 1.02-1.02), and the authors concluded that short-term exposure to PM 2.5 in Latin American cities is significantly associated with increased risk of respiratory mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, air pollution and its effects on health are considered to be a public health problem. Nevertheless, very few studies have been conducted in Latin America on the effects of air pollution on health, particularly with regard to morbidity [9]. …”
Section: Introductionmentioning
confidence: 99%
“…In aerodynamic terms, fine particulate matter ≤2.5 μm (PM2.5) in diameter has been held responsible for being the major air pollutant. Pulmonary diseases including lung cancer, chronic obstructive pulmonary disease and allergic asthma have been found to be caused by exposure to PM2.5, resulting in considerable morbidity and mortality (Fajersztajn, Saldiva, Pereira, Leite, & Buehler, ; Raaschou‐Nielsen et al, ; Xing, Xu, Shi, & Lian, ). Children, the elderly and individuals with pre‐existing pulmonary disease are particularly vulnerable (Anderson, Atkinson, Bremner, & Marston, ; Mathieu‐Nolf, ).…”
Section: Introductionmentioning
confidence: 99%